Prejudykaty prawa kościelnego biskupa Wacława z 1415 roku - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The precedential judgments 47 attached to the law of the church of Wrocław’s bishop Waclaw of 1415 Wenzeslauische Kirchenrecht have not so far been the subject of scientific reflection. The author presents their content in sequence and concludes that only two thirds of them were related to the matrimonial property law regulations of this Silesia’s law monument, while the remaining part were related to criminal law.
Keywords: Silesian law; church law; precendial judgements